1990
DOI: 10.1210/endo-127-1-245
|View full text |Cite
|
Sign up to set email alerts
|

Antigonadotropic and Antisteroidogenic Actions of Peroxide in Rat Granulosa Cells*

Abstract: Reactive oxygen species are produced in the ovary. In luteal cells, peroxide abruptly inhibits LH-sensitive cAMP and progesterone production, and may serve a role as a mediator of luteolysis by such mechanisms. The objective of the present studies was to evaluate the acute actions of peroxide in rat granulosa cells. Peroxide at concentrations in the low micromolar range produced a marked and dose-dependent inhibition of FSH-sensitive cAMP accumulation and progesterone production, and depleted cell levels of AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(34 citation statements)
references
References 30 publications
3
30
1
Order By: Relevance
“…In this research, the levels of these enzymes were significantly (P<0.05) inhibited by DON compared with the control, indicating that DON could induce oxidative stress in laying hens. This result is consistent with the previous research described above, and studies have also found that oxidative stress affects the female reproductive system by inhibiting follicle cell growth [26,27] or by even damaging ovarian and uterine cells. This is the probable explanation for why the DON group exhibited a lower egg production rate (71.15%) compared with the other groups.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In this research, the levels of these enzymes were significantly (P<0.05) inhibited by DON compared with the control, indicating that DON could induce oxidative stress in laying hens. This result is consistent with the previous research described above, and studies have also found that oxidative stress affects the female reproductive system by inhibiting follicle cell growth [26,27] or by even damaging ovarian and uterine cells. This is the probable explanation for why the DON group exhibited a lower egg production rate (71.15%) compared with the other groups.…”
Section: Discussionsupporting
confidence: 94%
“…The selenium nanoparticle (SeNP), which is one form of elemental selenium (Se0), has lower toxicity and better absorption and it is most effective when provided to broiler chicken under oxidative stress with the same dose but different sources of Se (organic, inorganic and nano-Se) [28]. According to some studies, the size of SeNPs synthesized by microorganisms has mostly been between 20 and 300 nm [20,26,27], and the diameter of the SeNPs in this research was 50 to 110 nm, which is consistent with previous research.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the survival of follicles subjected to gonadotropin stimulation is related to an increase in the expression of antioxidant enzymes (Tilly & Tilly 1995), while treatment with antioxidants blocks granulosa cell apoptosis in cultured follicles (Tilly 1996). Among the most noteworthy deleterious effects of ROS on follicular cells is the inhibition of induction of steroidogenesis by gonadotropic hormone with the loss of follicular function (Margolin et al 1990). …”
Section: Introductionmentioning
confidence: 99%
“…2 It is shown to have marked antigonadotropic activity in luteal and granulosa cells and blocks basal and stimulated progesterone production. 3,4 In the thyroid gland, H 2 O 2 plays an important role in the thyroid hormone synthesis. 5 As a reactive oxygen species, it is generated from nearly all sources of oxidative cycle and has the ability to diffuse in and out of cells and tissues.…”
Section: Introductionmentioning
confidence: 99%